NSDNA: a manually curated database of experimentally supported ncRNAs associated with nervous system diseases. Issue Volume 45:Issue D1(2017) (24th November 2016) - Wang, Jianjian; Cao, Yuze; Zhang, Huixue; Wang, Tianfeng; Tian, Qinghua; Lu, Xiaoyu; Lu, Xiaoyan; Kong, Xiaotong; Liu, Zhaojun; Wang, Ning; Zhang, Shuai; Ma, Heping; et al.
Abstract: The Nervous System Disease NcRNAome Atlas (NSDNA) (http://www.bio-bigdata.net/nsdna/ ) is a manually curated database that provides comprehensive experimentally supported associations about nervous system diseases (NSDs) and noncoding RNAs (ncRNAs). NSDs represent a common group of disorders, some of which are characterized by high morbidity and disabilities. The pathogenesis of NSDs at the molecular level remains poorly understood. ncRNAs are a large family of functionally important RNA molecules. Increasing evidence shows that diverse ncRNAs play a critical role in various NSDs. Mining and summarizing NSD–ncRNA association data can help researchers discover useful information. Hence, we developed an NSDNA database that documents 24 713 associations between 142 NSDs and 8593 ncRNAs in 11 species, curated from more than 1300 articles. This database provides a user-friendly interface for browsing and searching and allows for data downloading flexibility. In addition, NSDNA offers a submission page for researchers to submit novel NSD–ncRNA associations. It represents an extremely useful and valuable resource for researchers who seek to understand the functions and molecular mechanisms of ncRNA involved in NSDs.